THE EFFECT OF THE CULTURAL ORGANIZATION, LEADERSHIP, JOB SATISFACTION, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR LECTURER IN THE CHRISTIAN UNIVERSITY OF INDONESIA - NADEAK, G. BERNADETHA (Jurnal Ilmiah Educational Management, 2016)
The objective of this research is to study the effect of the cultural organization, leadership, job satisfaction, and organizational citizenship behavior lecturer in the Christian University of Indonesia. Quantitative approach used in this research with survey method. The samples of this research were one hundred and thirty one teachers and student selected randomly. The data were obtained by distributing questionnaire and analyzed by using path analysis. The result of the research can be conclude that: (1) the culture organization, leadership and job satisfaction had a positive direct effect on organizational citizenship behavior (OCB); (2) the culture organizational and leadership had a positive direct effect on task job satisfaction. Thus, the steakholders on campus UKI need to take concrete steps to ensure that in a campus environment with a culture and values that guarantee the existence of the Christian University of Indonesia campus in the future.